Синтез нейрорегулятора Model Reference Controller для системи наведення і стабілізації - Кузнецов, Б.І.; Василець, Т.Ю.; Варфоломієв, О.О. (Електротехніка і електромеханіка, 2015)
Виконано синтез нейрорегулятора на основі еталонної моделі для рішення задачі управління спеціальним устаткуванням рухомих об’єктів . Наведено порядок синтезу нейрорегулятора Model Reference Controller, реалізованого в пакеті прикладних програм Neural Network Toolbox системи MATLAB . Встановлено, які параметри нейрорегулятора
суттєво впливають на якість регулювання і визначені значення параметрів, що забезпечують найкращі показники
якості функціонування системи. Виконано моделювання системи на ЕОМ. Выполнен синтез нейрорегулятора на основе эталонной модели для решения задачи управления специальным оборудованием подвижных объектов. Приведен порядок синтеза нейрорегулятора Model Reference Controller, реализованного в пакете прикладных программ Neural Network Toolbox системы MATLAB. Установлено, какие параметры нейрорегулятора
существенно влияют на качество регулирования и определены значения параметров, которые обеспечивают лучшие
показатели качества функционирования системы. Выполнено моделирование системы на ЭВМ. The aim of this work is the synthesis of neural network reference
model controller. The synthesis is performed in MATLAB for the
problem of control of the aiming and stabilization system for the
special equipment of moving objects. This paper presents the
synthesis of the neural network reference model controller to
meet the given performance characteristics of operation for the
aiming and stabilization system for the special equipment of
moving objects. Simulink tool in MATLAB is used to build the
block diagram of double-loop neural network system of aiming
and stabilization, where the reference model controller is put in
the velocity loop and P-regulator is put in the position loop,
with feedforward velocity control. Presented the method of synthesis of the neural network reference model controller that is
implemented in the Neural Network Toolbox in MATLAB. System tests with the broad range of parameter values determined
the key parameters defining the control quality. Optimal values
of the key parameters were found to provide the highest control
performance. System simulation and analysis of the obtained
results is given.